MODELLING THE EFFECT OF A THERMOELECTRIC DEVICE ON THE FOOT UNDER AMBULATORY CONDITIONS - M. A. Khazamova; D. A. Magomedov; D. N. Kobzarenko (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives This work was devoted to the research of thermal processes that occur in the reflex areas of the human body, in particular, in reflexogenic areas of the human foot, under the thermal influence under ambulatory conditions.Method A model of thermal impact on the reflex areas of the human body was developed on the basis of a semiconductor thermoelectric device. A simplified physical model was studied, which does not consider heat exchange in thermoelectric batteries (TEBs) and elements of TEBs pairing with separate reflex zones.Results Diagrams for temperature distribution throughout the foot at different values of heat flow and diagrams of temperature changes over time were obtained. The thermal influence of a TEB brought in thermal contact with the opposite surface of the foot is negligible in this case; this is due to the low thermal conductivity of foot tissues, as well as insignificant thermal flows on its surface (low-power TEBs were used for such procedures).Conclusion The developed model of a semiconductor thermoelectric device for treating the reflex areas of the human body – in particular, the foot – allows an investigation of thermal processes occurring during the thermal treatment of biologically active points of the human sole. It is established that local temperature impact on a biological object does not result in significant temperature difference over its thickness.